Sistem Informasi Koperasi Berbasis Web dengan Dashboard Monitoring dan Laporan Terintegrasi (studi kasus : Koperasi Tunas Mandiri Sejahtera) - M Yusuf Abdurrahman M Yusuf Abdurrahman (Universitas Lampung, 2026)
Tunas Mandiri Sejahtera Cooperative still manages member data, transactions, and financial reports manually, resulting in inefficient administrative processes, recording errors, and delays in report generation. This study aims to design and develop a web-based Cooperative Information System equipped with a monitoring dashboard and integrated reporting. The research employed the Research and Development (R&D) method using the Waterfall development model. The system was developed using PHP, the CodeIgniter framework, and MySQL database, and was tested using the Black Box Testing method. The results show that the system is capable of managing member data, transactions, and financial reports in an integrated manner while providing real-time information through a monitoring dashboard. The implementation of the system improves data management efficiency, accelerates report generation, reduces recording errors, and supports more effective decision-making.